2012
DOI: 10.1371/journal.pgen.1002603
|View full text |Cite
|
Sign up to set email alerts
|

Balanced Codon Usage Optimizes Eukaryotic Translational Efficiency

Abstract: Cellular efficiency in protein translation is an important fitness determinant in rapidly growing organisms. It is widely believed that synonymous codons are translated with unequal speeds and that translational efficiency is maximized by the exclusive use of rapidly translated codons. Here we estimate the in vivo translational speeds of all sense codons from the budding yeast Saccharomyces cerevisiae . Surprisingly, preferentially used codons are not translated fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
327
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(354 citation statements)
references
References 75 publications
(122 reference statements)
25
327
1
1
Order By: Relevance
“…This calculation quantifies the expectation that tRNAs expressed at lower abundances or that involve non-standard base pairing in their codon-anticodon interaction should require longer to translate. Consistent with previous reports [13,23,31,32], all CHX experiments report weak experiments from many different studies in yeast, grouped by hierarchical clustering. Red indicates positive correlation and blue indicates negative correlation.…”
Section: Pretreatment With Cycloheximide Consistently Changes Enrichmsupporting
confidence: 89%
“…This calculation quantifies the expectation that tRNAs expressed at lower abundances or that involve non-standard base pairing in their codon-anticodon interaction should require longer to translate. Consistent with previous reports [13,23,31,32], all CHX experiments report weak experiments from many different studies in yeast, grouped by hierarchical clustering. Red indicates positive correlation and blue indicates negative correlation.…”
Section: Pretreatment With Cycloheximide Consistently Changes Enrichmsupporting
confidence: 89%
“…For instance, the tRNA pool in mammals appears to be equally efficient at translating any transcriptome, regardless of cell type or condition (Rudolph et al 2016). While some works have suggested that preferentially used codons are not translated faster than unpreferred ones or that rare codons do not correlate with ribosome pausing (Qian et al 2012;Guo et al 2010;Pop et al 2014), other reports have suggested that differences in tRNA population are associated with diverse effects on translation (Lampson et al 2013;Goodarzi et al 2016). This is the case of a mutation of a tissue-specific tRNA expressed in the mouse nervous system, which led to ribosome stalling and that was implicated as the cause of neurodegeneration (Ishimura et al 2014).…”
Section: Translation Kineticsmentioning
confidence: 99%
“…Cellular fitness can also be affected by codon-tRNA balance [69]. Gingold et al [70] investigated this notion and revealed that the levels of endogenous tRNAs adapt to match the codon usage of mRNAs specifically expressed in differentiated versus proliferating cells.…”
Section: Pr Ospects and Overviewsmentioning
confidence: 99%